The Design of Home Decor Products to Reflects Fun from Costumes Dancers of Country Music Bands - Ragyart, Anakkanon; Arrayaphaon, Patave (Journal of Fine and Applied Arts Khon Kaen University, 2021)
The objective of this research was to study the model of the trumpet set, country music bands and to find ways to design products for home decoration that reflect the liveliness of the dancers’ costumes. The target groups included key informants, casual Informants and general Informants in the field of country music dancers’ costumes and product design specialists. Data was collected using the survey, observation, interview and opinion assessment tools. Analytic induction was employed to acquire average and standard deviation. The result of the study suggested that the country music dancers’ costumes could be linked to the design of home decoration products, with the essential elements being the form, the colours and the materials. The design directions can be specified in two concepts; “prominent radiance” and “movable and lively mechanism”. The result of the research on the design of home decoration products showed the two directions could reflect the fun and led to the creation of 6 design guidelines. In general, the experts rated the appropriateness at a high level. The tendency of commercialization was ranked the highest with the mean of 5.00 and the SD = 0.00. Considering the direction of the concept, it was found that the concept ‘prominent radiance’ was rated the most appropriate at the overall level. In a more specific findings, the 2nd (A2) method gained the “most suitable” opinion, with mean = 4.44, and the SD = 0.60. The concept ‘movable and lively mechanism’ was given a “highly appropriate” opinion. More specifically in terms of guidelines, it was found that 4 (B1) method was very appropriate with highest mean = 4.33 and the SD = 0.68.